Laparoscopic Approach to Giant Over Cysts and Case Report - Baha ARSLAN; Varlık EROL; Tuğba Han YILMAZ; Hüseyin GÜLAY (Bezmiâlem Science, 2018)

(untitled)
Tumor behavior plays an important role when abdominal masses approach. Minimally invasive surgery in patients who are thought to be benign is a valuable approach to comfort patients and surgeons. In the light of the literature, we examined a laparoscopic surgical approach in a premenopausal patient who applied to our clinic for swelling in her abdomen and whose mesenteric and over cysts were not completely differentiated.